Performance analysis of OFDM system in AWGN and practical Rayleigh fading channels - Iskander, Ghadeer1 Haider; Jabbar, Ahmed N.; . Murdas, Ibrahim A (International Journal of Engineering and Technology, 2018)
In this work, a multi-parameters OFDM communication system has been simulated to analyze and study the performance and behavior of the OFDM over practical distorting noisy channels. The analysis covered in this research includes the QAM-levels, the SNR, and the number of the FFT subcarriers. These parameters were tested over practical ITU channels to examine the OFDM performance under mildly distorting channel using the In-Door channel, moderately distorting channel using the Out-Door channel and severely distorting channel using the GSM channel models. The performance was measured using the Bit Error Rate (BER). This analysis includes for the first time the connection between these various parameters; the SNR, the subcarriers and the QAM levels, into three dimensional surface to give the reader a deep sight to the OFDM behavior. Adding to that, we introduced the connection between the QAM-levels and the Peak to Average Power Ration (PAPR) and why sometimes we should resort to higher QAM-levels despite the increase in BER. This research, also, describes step by step the creation of practical OFDM system using the Simulink for further analysis.